TEACHERS’ BELIEFS IN THE USE OF FORMATIVE ASSESSMENT IN K 13(2013 CURRICULUM) - Salmiati, Salmiati; Sauhana, Felci Tria; Ahmad, Ahmad (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
Believe in formative assessment is very important to increase the students’ achievement, and to increase not only the quantities of students but also the qualities of them.  This research aims to explore the teachers’ beliefs in the use of formative assessment based on K13 (2013 curriculum). By using qualitative approach, this case study utilized classroom observations and individual semi-structured interviews with data analyzed. Three junior high schools English teachers as sampled in this research and result of the research showed that basically all the teachers believed in the use of formative assessment to motivate the students’ achievement. However, in implementing it based on K13 (2013),  it was limited by the students’ background knowledge. The findings show that there were gaps between the  definitions believed by the teachers to the application of the formative assessment in the classroom.